Caracterización de las tomas de agua del sistema morning glory en el embalse La Regadera. (2023)
The purpose of this investigation was to characterize the water contained in the La Regadera reservoir using the Morning Glory system. The need to characterize the water resource arises from an emergency that occurred in November 2020, the water that arrived to be made drinkable had high levels of turbidity, apparent color, iron content, manganese content and ammonium content, through the characterization of the raw material, we seek to have more information about the water contained in the reservoir and the behavior of the physicochemical parameters. The above was done by taking samples from the different valves located at different depths of the reservoir, determining their characteristics (turbidity, apparent color, pH, ammonium, iron and manganese), through different physicochemical analysis techniques, as well as The factors that influence the quality of the water contained in the reservoir were analyzed, such as precipitation and the movement that could be generated in the waters of the dam caused by the speeds and direction of the wind.